Intermarriage of Asian Americans in the New York City region: Contemporary patterns and future prospects - Liang, Z.; Ito, N.
tbls.
pp. 876-900
Keywords: Inmigración; Siglo XX; New York; Matrimonio; Asiaticos; Americanos